The prognostic value of the controlling nutritional status score in patients with multiple myeloma. Issue 8 (2nd July 2020) - Kamiya, Takahiro; Ito, Chisako; Fujita, Yuriko; Ogura, Shinji; Mizuno, Kota; Sakurai, Aki; Aisa, Yoshinobu; Nakazato, Tomonori
Abstract: The Controlling Nutritional Status (CONUT) score predicts the prognosis in several tumors. However, its prognostic significance in multiple myeloma (MM) remains unclear. The present study investigated the correlation between the CONUT score and the survival outcomes of MM patients. A total of 178 patients newly diagnosed with MM were retrospectively enrolled. Patients with a high CONUT score (≥5) had a significantly shorter median overall survival (OS) than those with a low CONUT score (≤4) (33 vs. 57 months, p < .001). In a multivariate analysis among patients with International Staging System (ISS) score of ≤2, a high CONUT score was an independent prognostic covariate for the OS after adjusting for other significant factors (hazard ratio 2.364; 95% confidence interval 1.324–4.220, p = .004). Our results suggest that the CONUT score is a predictor of a poor outcome in patients with MM, particularly in low-ISS-score cases.